Determinants of dissemination of environmental information: an empirical survey - Giannarakis, Grigoris; Zafeiriou, Eleni; Sariannidis, Nikolaos; Efthalitsidou, Kyriaki (Journal of Business Economics and Management, 2016)
The major objective of the present paper is to identify the factors that influence the dissemination of environmental information. In particular, analyst stock recommendation, country level risk, corporate value and environmental performance are surveyed as determinants of the environmental dissemination level. The survey was based on a sample of 92 multinational firms for the period 2009–2013, longer than that used in most past works. The methodology employed on our data is the panel data analysis with fixed effects. As proxies, for the dissemination level of environmental information, two different environmental disclosure indexes are used the Environmental Disclosure Score and Carbon Disclosure Leadership Index. According to our findings, the environmental performance in terms of Emission Reduction Initiatives and the country’s risk premium affects in a positive way the dissemination of environmental disclosures while the results regarding the stock analyst recommendation are controversial. Another important finding is that the firm’s value is validated as an insignificant factor for the dissemination level of environmental information. The aforementioned results provide the corporate managers with a tool to attract environmental friendly investors. The novelty on the present manuscript stands on the use of proxies for the environmental performance; namely the first one is based on outcome – objective while the second one refers to the corporate intention, elements that enrich the existing literature in the field of environmental behavior and dissemination of the environmental information of a firm.